2019
DOI: 10.3390/w11102187
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Water Virology: Hierarchical Bayesian Modeling for Estimating Virus Inactivation Curve

Abstract: Hazard analysis and critical control point (HACCP) are a series of actions to be taken to ensure product consumption safety. In food poisoning risk management, researchers in the field of predictive microbiology calculate the values that provide minimum stress (e.g., temperature and contact time in heating) for sufficient microbe inactivation based on mathematical models. HACCP has also been employed for health risk management in sanitation safety planning (SSP), but the application of predictive microbiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 52 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…The prediction results of the coxsackievirus and echovirus models implied that the strain type was an important factor for predicting enterovirus LRVs (Fig. 4), so the hierarchical Bayesian approach, 21 which took more than three types of strain into account, was likely to improve the LRV prediction for the poliovirus. In addition, it is possible to take into account the effect of experimental conditions, which are not recorded in the articles on the LRV prediction by the approach.…”
Section: Does the Hierarchical Bayesian Approach Improve Models?mentioning
confidence: 99%
See 2 more Smart Citations
“…The prediction results of the coxsackievirus and echovirus models implied that the strain type was an important factor for predicting enterovirus LRVs (Fig. 4), so the hierarchical Bayesian approach, 21 which took more than three types of strain into account, was likely to improve the LRV prediction for the poliovirus. In addition, it is possible to take into account the effect of experimental conditions, which are not recorded in the articles on the LRV prediction by the approach.…”
Section: Does the Hierarchical Bayesian Approach Improve Models?mentioning
confidence: 99%
“…In addition, it is possible to take into account the effect of experimental conditions, which are not recorded in the articles on the LRV prediction by the approach. 21 The probability distributions of the LRV of each virus species were determined based on AIC (Table S2 †). The variables selected by the best fit models based on the regularized regression analyses (Table 4) were applied here.…”
Section: Does the Hierarchical Bayesian Approach Improve Models?mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the disinfection intensity that achieves the target LRV needs to be determined by taking water quality and operational information at each WWTP into account. Previously, we proposed the concept of predictive water virology, in which the models predicted virus LRV by using water quality and operational parameters as explanatory variables ( Kadoya et al., 2019 ). The predictive water virology enables us to derive the appropriate CL to attain the target LRV under site-specific water quality.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive water virology enables us to derive the appropriate CL to attain the target LRV under site-specific water quality. Kadoya et al. (2019 and 2020) previously proposed the concept of predictive water virology and reported that the predictive inactivation models, based on hierarchical Bayesian modeling (HBM) and regularized regressions, flexibly correspond to the changes and variety in water quality parameters among WWTPs ( e.g., seasonal variation).…”
Section: Introductionmentioning
confidence: 99%